Association of MMP-9 promoter polymorphism and breast cancer among Iranian patients - Toroghi, Fatemeh; Mashayekhi, Farhad; Montazeri, Vahid; Saedi, Hanid Saeedi; Salehi, Zivar (European Journal of Oncology and Environmental Health, 2017)
Background and aims: Breast cancer is one of the most common cancers in women population. This cancer is influenced by environmental and genetic factors. MMP-9, a member of MMPs family, is located on 20 q11.2- q13.1 and encodes Gelatinase B, a 92 KDa protein which is able to degrade collagen IV, matrix proteoglycan core and elastin. Over expression of MMP-9 has been shown in some cancers. MMP-9 is involved in the metastasis and cancerous cells migration. MMP-9 promoter polymorphism (-1562 C>T) is a candidate for cancer susceptibility. It is likely that T allele impedes recruitment of repressor proteins and causes gene over expression in T allele carriers. In the present case-control study we investigate whether MMP-9 promoter polymorphism (-1562C>T) is associated with breast cancer. Methods: A total of 216 Azeri women including 104 patients and 112 healthy women were enrolled in the study. Blood sampling was done after taking a written consent. Genomic DNA was extracted and its purity was determined on 1% agarose gel. Then the given polymorphism was determined by PCR- RFLP method using SphI. Results: The results showed that T allele and CT genotype are more frequent in the patients as compared to the control group, but there are not significant differences between two groups (P=0.1). Conclusion: It is suggested that MMP-9 polymorphism (-1562C>T) is not associated with the breast cancer occurrence in our population. However, further studies in larger populations including other genetic and environmental factors are required to achieve conclusion.